Mimesis, kenōsis e autoreferenzialità - Antonelli, Emanuele (Bollettino Filosofico, 2015)
In this paper we offer an interpretation of the inner relationship between nihilism and the tragic. With reference to the work of Heinz von Foester and to the sciences of complexity, we will argue that the essential feature of the tragic is “autoreferentiality”. Furthermore, arguing in favor of the use of the theological notion of kenōsis as the most precise description of the “history of nihilism”, we will show that the latter is to be understood in terms of the “weakening”, or loweringof all the reference points generated by autotranscendent, etheronomous, social phenomena. The consequence of nihilism is therefore autoreferentiality. This result will offer the opportunity to see both to what extent we are now, at the end of modernity, living a tragicsituation and, eventually, to claim – by recalling that autoreferentiality is also the inner logic of freedom – that the tragic is the outcome of modernity, but not a necessary one.